The Conservative Project to 'Break the Link between British Courts and Strasbourg': Rhetoric or Reality?. Issue 6 (20th November 2017) - Fenwick, Helen; Masterman, Roger
Abstract: The Conservative party has repeatedly pledged to replace the HRA with a British Bill of Rights, with the aim of 'breaking the link' between domestic courts and Strasbourg. This article examines the implications of this proposal, the nature of the current relationship with the European Court, and the extent to which the link has already been weakened. It considers the bases of the Conservative proposal, and the options available in breaking that link in a Bill of Rights, taking account of the potential introduction of limitation clauses and the possibility of according Strasbourg judgments against the UK an advisory status only. Finally, taking account of the European Court's recent movement towards 'enhanced' subsidiarity, it will examine the consequences for the protection of human rights of reliance on a Bill of Rights intended to be interpreted and applied independently of Strasbourg influence.